(untitled) (Journal of Applied Learning and Teaching, 2024)
Technology is no longer a tool but a skill. Teaching is a challenge in the age of Generative Artificial Intelligence (AI). However, the real problem seems to be not about what to teach but how to teach. So, this opinion piece aims to answer the following research question (RQ): How should we teach Generation AI? In this opinion piece, I share some teaching notes and propose five recommendations for AI use in education, especially in legal education.